Analisis Kebijakan Perlindungan Data Pribadi Di Kota Bengkulu: Studi Implementasi UU PDP Dalam Era Digital - Wanda Dwi Cahyani; Anita Marianata (CV. ITTC INDONESIA, 2024)
aspects of life, but it also increases the risk of personal data leakage. This research aims to analyze the challenges in the implementation of the Personal Data Protection Law (UU PDP) Number 27 of 2022 in Bengkulu City as well as the level of public awareness of personal data protection. The research method used is content analysis of news articles related to data leakage and interviews with the public. The results showed that data leakage in Bengkulu City includes sensitive information, such as financial data and personal identity, due to weaknesses in digital security systems and low awareness of data protection. Interviews revealed that 65% of the public did not have a deep understanding of personal data protection, while 50% did not know the details of the PDP Law. Key challenges identified include weak law enforcement, lack of supervision of digital service providers, inadequate infrastructure, and low digital literacy. This study recommends enhancing cybersecurity, strict law enforcement, massive socialization, and strengthening digital infrastructure to create a safe environment for personal data protection in Bengkulu City